Box-Behnken design based optimization of phenolic extractions from Polygonum equisetiforme roots linked to its antioxidant and antibacterial efficiencies - Elgudayem, Farah; Aldiyab, Abdullah; Albalawi, Marzough Aziz; Omran, Awatif; Kafkas, Nesibe Ebru; Saghrouchni, Hamza; Var, Işil; Rahman, Md Atikur; El Sabagh, Ayman; Sakran, Mohamed; Ben Ahmed, Chedlia (Frontiers in Sustainable Food Systems, 2023)
The aim of this study was to optimize the ultrasonic aqueous extraction of phenols from Polygonum equisetifome roots using Box-Behnken design. The extraction temperature (30-70 °C), Ultrasound Assisted Extraction (UAE) time (1-9 min), and liquid-solid ratio (35-45 mL/g) were investigated as the factors that influence the phenolic yield (Y1) and their DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging activity (Y2). The optimal conditions for both responses were 50 °C, 5 min, and 40 mL/g. At these conditions, Y1 reached its maximum to be 45.321 mg GAE/g dry weight and Y2 to be 120.354 µmol Trolox/g dry weight. In addition, anthocyanin, condensed tannins content, FRAP (Ferric-reducing/antioxidant power), and ABTS scavenging activity were determined. The morphological and physico-chemical features of the extract were analyzed using SEM-EDX and FT-IR analysis. The antibacterial activity of the extract showed that the extract is more efficient against Gram-positive strains. The UAE confirmed as a reliable, efficient and time-saving technique for the extraction of water-soluble phenolic compounds. The eco-friendly extraction of these compounds can be used in the food and pharmaceutical industries as a precious source of antioxidants.